Philippine labor standards guidebook - Solidum-Protacio, Sally (Quezon City : C & E Pub., 2010)
The book is purposely outlined by subject matter rather than by chronological arrangement of the Labor code.
CHAPTER 1. Labor law and social legislations -- 2. Employer-Employee Relationship -- 3. Contracting and subcontracting -- 4. Working hours -- 5. Rest periods -- 6. Workers Leave benefits -- 7. Wages -- 8. Minimum Wage -- 9. 13th Month Pay -- 10. Service charge -- 11. Retirement Pay -- 12. Separation Pay -- 13. Social Security Benefits (RA 8282) -- 14. Employees compensation program -- 15. Philippine Health Insurance Corporation - 16. PAG-IBIG -- 17. Working conditions for special groups of employees -- 18. Sexual Harassment -- 19. Employment/work permits an working visas for Aliens -- References -- Index.
Includes bibliographical references and index.
Keywords: LABOR LAWS AND LEGISLATION -- PHILIPPINES